Víctor Manuel Arbeloa Muru - Virto Ibáñez , Juan Jesús (Huarte de San Juan. Geografía e Historia, 2014)
Víctor Manuel Arbeloa was born in Navarra (Spain). He studied for the priesthood in Pamplona, Comillas and Rome. As a priest, he divides his time between priestly duties and historical research through the archives and libraries of the country and overseas. He was affiliated with the Spanish Socialist Party (PSOE) in 1977 and he retired from politics in 2000. Several books from his Bibliography regarding Navarra, the Freemasonry, the Statute of Autonomy of the Basque Country and the Socialism during the II Spanish Republic (1931-1936) are highlighted.
Keywords: Freemasonry; Spanish Socialism; The House of the People; Navarra; the Statute of Autonomy of the Basque Country; II Spanish Republic; The Church in Spain; Clericalism-Anticlericalism